Spread of the qnrVC Quinolone Resistance Determinant in Vibrio cholerae - Fonseca, Érica Lourenço da (2011)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Genética Molecular de Microrganismos. Rio de Janeiro, RJ. Brasil.